Efficacy of ASTM saturation techniques for measuring the water absorption of concrete - Safiuddin, M.; Mahmud, H.B.; Jumaat, Mohd Zamin (Arabian Journal for Science and Engineering, 2011)
The aim of this study was to compare the efficacy of three ASTM saturation techniques for measuring the water absorption of concrete. The water absorption of two ordinary concretes was determined based on the cold water, boiling water and vacuum saturation techniques. The concretes were produced with water to cement (w/c) ratios of 0.50 and 0.60 and tested at 7 and 28 days. The vacuum saturation was more effective than the cold water and boiling water saturation methods. The vacuum saturation technique produced up to 13.1 more water absorption than the boiling water saturation method and up to 20.2 more water absorption than the cold water saturation method. Thus the present study suggests that the vacuum saturation technique is more efficient than both cold water and boiling water saturation methods to measure the water absorption of concrete.